RESEARCH OF THE PRAGMATIC FUNCTIONS OF SOMATIC PHRASEOLOGY IN TRANSLATION ISSUES (Scientific journal of the Fergana State University, 2023)
The article is devoted to the study of the matters of the somatic phraseological units in pragmatic aspect as one of the branches of linguistics. Concentrating on their function we were studied pragmatic aspects of cultural codes. In the communicative process of somatic phraseological units, the emotional feelings, desires, circumstances and the state of the speaker to the listener were assessed. It discusses the lingopragmatic aspects of phraseological units with somatic components in Uzbek, Russian and English. Translation is the right way to communicate, and pragmatism is how to use the language correctly in communication. He analyzed various approaches to cultural linguistics, pragmatic understanding and the relationship between culture and language.